Parameters of Heart Rate Variability Can Predict Prolonged Asystole before Head‐Up Tilt Table Test. Issue 5 (4th March 2014) - Gursul, Erdal; Bayata, Serdar; Tuluce, Selcen Yakar; Berilgen, Rida; Safak, Ozgen; Ozdemir, Emre; Tuluce, Kamil
<x xml:space="preserve">Abstract</x> Background We aimed to evaluate whether heart rate variability (HRV) could predict prolonged asystole before head‐up tilt table test (HUTT) by comparing time domain HRV parameters of patients with type 2B vasovagal syncope (VVS) and patients with other types of VVS. Methods Ninety‐eight patients who examined with 24‐hour Holter electrocardiogram monitoring before HUTT and diagnosed with VVS were enrolled. Patients were divided into two groups in accordance with their VVS type as group 1 (n = 43) consisting of patients with type 2B VVS and group 2 (n = 57) consisting of patients with other types of VVS. Time domain HRV parameters (SDNN, SDANN, SDNN index, RMSSD, pNN50) of two groups were compared. ROC curve analysis was performed to predict best cutoff values that could prognosticate occurrence of prolonged asystole during HUTT. Results SDNN, SDANN, SDNN index values were significantly longer for group 1 compared to group 2 (P = 0.009, P = 0.006, P = 0.004; respectively). While a SDNN cutoff value of ≥151 ms predicted occurrence of type 2B VVS before HUTT with 69% sensitivity and 56% specificity, a SDANN value of ≥164 ms had 47% sensitivity and 87% specificity and a SDNN index value of ≥102 ms showed 40% sensitivity and 85% specificity. Conclusions In our study, we tried to demonstrate prediction of prolonged asystole by analyzing HRV parameters before HUTT. We found out that time domain HRV parameters were longer in patients with type 2B VVS than patients with other types of VVS. Our results need to be supported by extensive studies.